Obrazy. 6. Andrej Michajlovič Lobanov, o del nomadismo: Profili di registi della seconda generazione russa - Lenzi, Massimo (Mimesis Journal, 2016)
This is the last part of the essay dedicated to Andrei Lobanov Mikhailovich (1900- 1959), a distinguished director-pedagogue (teacher at gitiS for Henrikas Vancevičius, Andrei Goncharov and Georgy Tovstonogov, among others) and author, between 1931 and 1958 of some theatrical productions that would exert a great in uence on the Russian theater up to these days. Here is rebuilt the rst decade of his training and theatrical activities, conducted in Moscow in various Studios (Science and Art, Gejrot, Chaliapin, Second Studio of the Mat, Our Studio, Zavadsky, Simonov), theatrical institutions (Theatre VF Komissarževskaja, Experimental Theatre State Drama) and its relationships with many of the protagonists of that extraordinary period of the theatre life in Moscow.